An evaluation of directly compressible tablet bases on the performance of ibuprofen tablets - Vawda, Naseem (My University, 2001)
Ibuprofen is a phenylpropionic acid derivative, which has analgesic, antiinflammatory and antipyretic actions. It is used in the management of mild to moderate pain, inflammatory conditions, peri-articular disorders, musculoskeletal disorders and joint disorders. Tablets, like ibuprofen, can be manufactured by three different processes viz. wet granulation, dry granulation and direct compression. With direct compression, the directly compressible base, along with the active ingredient (ibuprofen) and other suitable excipients, can be compressed directly.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand , in partial fulfilment of the requirements for the degree of Master of Science in Medicine (Pharmaceutical affairs)
Keywords: Ibuprofen; Tablets; Cellulose